The Human Capital of Technicians in State University of Malang - Pratama, Aditya Yudha; nurhadi, didik (Teknologi dan Kejuruan: Jurnal Teknologi, Kejuruan, dan Pengajarannya, 2022)
Agencies or companies' ability to create and develop strategies to advance depend on human capital. It receives public attention as tangible state assets, policies, and organizations and are described as the core vital forces in the professional world. It is essential because it provides companies with some new skills, opportunities, and even development. This study aims to describe the human capital (knowledge, competence, skill, and innovation) of the technicians in the State University of Malang using a survey research design. The population is the technicians in the State University of Malang. The result indicates that the human capital in the State University of Malang can be categorized as follows: 3.1 percent of the technicians are very positive (one technician), 31.3 percent are (ten technicians), 34.4 percent are average (11 technicians), 28.1 percent are negative (nine technicians), and 3.1 percent are very negative (one technician). It can be concluded that the human capital of the State University of Malang is average, which implies that not all the employees can perform well at work and meet the indicators; hence, the need for improvement.